To play or not to play: How video games motivate gamers in Malaysia to play - Ng, Benedict Boon Yew (2023)
Video games have become a worldwide phenomenon despite only being roughly seven decades old, but due to the industry’s relative youth, we still have much to learn and understand about gaming as it is a constantly evolving field that is closely linked with the advancement of technology. It was estimated that Malaysia alone had 20.1 million gamers in 2019. With more than half the Malaysian population being gamers, it would be interesting to discover what motivates them to play video games. This study is an attempt to understand video games’ strong motivational pull through the analysis of the gaming experience of gamers in Malaysia by utilising Ryan, Rigby and Przybylski’s Player Experience of Need Satisfaction (PENS) (2006) model. Three focus groups consisting of a total of 15 gamers in Malaysia were gathered to discuss and share their personal gaming experiences for the purpose of this study. According to the findings, gamers were motivated to play video games because of their innate desire to overcome challenges to become better, to have the opportunities to take actions on their own accord, and to connect and interact with others. And games found with any of the following five attributes, to provide opportunities to mastering challenges; tell a heroic narrative; provide opportunities for action; provide a platform for companionship and social opportunities; or provide competitive play, would often keep the gamers coming back for more.